HUBUNGAN PENGETAHUAN DAN SIKAP PERAWAT DALAM PENATALAKSANAAN PEMBIDAIAN PASIEN FRAKTUR DI RS BHAYANGKARA PALEMBANG 2018 - Sasono Mardiono; Herwin Tri Putra (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2018)
Traffic accidents have been the concern of many parties. WHO data in 2015 the number of traffic accidents occurring in 180 countries have the most frequent fracture victims in the upper extremity by 36, 9% and lower extremities of 65.2%. The high rate of incidence of fractures can affect the length of time in hospital so require urses who have good competence. This study aims to know the relationship of knowledge and attitude of nurses in the splint management of fracture patients. The location of research was at Bhayangkara Hospital in IGD and Jana Nuraga . This research was a quantitative research with cross sectional design. The sample in this research amounted 32 respondents selected by using total sampling technique. The data in this research was obtained by using questionnaire instrument, then analyzed by using chi square test. This research was conducted on April 26th -May 11th , 2018 held at Bhayangkara Hospital Palembang. The result of data analysis showed the correlation between knowledge and attitude in the management of the fracture in the IGD and the Jana Nuraga 2 Hospital Bahyangkara Palembang with the value (p value <0,005). It is expected thatthe Bhayangkara Palembang Hospital to continue to improve the knowledge of nurses by through various training and seminars especially in the treatment of fractures so as to generates nurses who have the competence of skill in providing services to the fracture patient